The Scenic Aleph: The Temporal System of the Video-Scenic Screen - Montes Rodríguez, Gustavo; Sanz de León, Vicente; Santana Mahmut, Saida (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The aim of this article is to determine the modifications that the audiovisual projection screen introduces in the temporal component of the video-scenic work. The methodological design links presuppositions of the Theatrical Theory and the Theory of Audiovisual Narration and resorts to the dramatological analysis model to approach concrete video-scenic plays. The introduction of the audiovisual screen implies an extension of the temporal flexibility of the drama, producing an expansion of the represented time through a multifocalized discourse, specific to the temporal system of the video-scenic play.